[Terry Farrell] (1984)
Contiene: Early Work - Hostel for overseas students 1968 - 40 Co-ownership flats 1970 - Rehabilitation study of 1,000 older council owned dwellings 1975 - The Colonnades 1974-76 - Housing Society Schemes 1972-80 - Factory Schemes 1972-80 - Clifton Nurseries Greenhouse Garden Centre and Shop 1979-80 - Clifton Nurseries Garden Shop and Public Park 1980-8 - Low Cost Timber Frame Housing 1974-81 - Urban Infill Factories 1979-81 - Architect´s own Offices 1980-81 - Craft Council Gallery and Information Centre 1980-81 - Private House 1978-81 - Festival Exhibition Building 1982 - Alexandra Pavilion 1980-81 - Water Treatment Centre 1979-82 - Vauxhall Cross National Competition 1982 - Television Broadcasting Centre 1981-82 - Radio Headquarters 1982-83 - Television Studios 1982-83 - The Triangles, Mansion House 1983-84 - Mixed Development of an Historic Triangular Island Site - Two Adjoining Corner Office Buildings - Banking Building - Offices and Banks 1983-86 - Clubhouse, Headquarters and Boat Store - Factory and Offices - Hammersmith Broadway 1984.
Keywords: FARRELL, TERRY; GRAN BRETAÑA; INGLATERRA; LONDRES; LIVERPOOL; ARQUITECTURA DEPORTIVA; URBANIZACIONES ESPECIALES; JARDINES MATERNALES; ESTUDIOS DE ARQUITECTOS; CENTROS DE INFORMACION; VIVIENDAS PARA ARQUITECTOS; EDIFICIOS PARA RADIODIFUSION; ESTUDIOS DE RADIO; EDIFICIOS PARA TELEVISION; ESTUDIOS DE TELEVISION; ALBERGUES; SOLADOS; EDIFICIOS DE VIVIENDAS; VIVIENDAS UNIFAMILIARES; VIVIENDAS MULTIFAMILIARES; INDUSTRIAS; HOSTERÍAS; HOTELES; AUDITORIOS; PABELLONES; CLUBES; ARQUITECTURA BANCARIA; BANCOS; EDIFICIOS DE OFICINAS; CONCURSOS; AGUA; ABASTECIMIENTO DE AGUA; PADDINGTON; REGENT'S PARK; WESTMINSTER; BAYSWATER; COVENT GARDEN; WOOD GREEN; JENCKS, CHARLES; DINGLE; HARINGEY; BERKSHIRE; READING; QUEEN STREET; HENLEY